Pengaruh kualitas pelaporan keuangan, kepemilikan institusional dan ukuran perusahaan terhadap asimetri informasi pada perusahaan perbankan yang terdaftar di bei tahun 2008-2012 - Kusuma, Tifany; Agusti, Restu; L, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to determine the effect of financial reporting quality, institutional ownership and firm size against the asymmetry of information on banking companies listed in Indonesian Stock Exchange in 2008-2012.The data used in this study are secondary data from financial data in the Indonesian Stock Exchange. The sample method used was purposive sampling, the population of 32 companies listed in the Indonesian Stock Exchange, research sample counted 14 companies that meet the criteria. Hypothesis testing is done by using multiple linear regression analysis.The results of this research base on hypothesis test indicates that the quality of financial reporting and institutional ownership has no significant effect to the asymmetry of information with significant are 0.955 and 0.338, while the firm size has significant influence to the asymmetry of information with significant is 0.040. The magnitude of the effect (Adj R-Square) of the quality of financial reporting, institutional ownership and firm size on asymmetry of information was 8.1%. While the remaining 91.9% is influenced by other variables.Keywords: information asymmetry, institutional ownership, firm size, the quality of financial reporting